Consciousness and applied linguistics theory and practice - Rustamov Elmirza, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The paper reviews the previous empirical studies on the important role of consciousness in second language acquisition (SLA) through stating the views of different authors, philosophers, scholars. Then, the role of consciousness in terms of concepts such as attention, awareness, intentionality, and control comes up for review. These concepts provide growing support for the view that the role of consciousness is vital for second language learning.